uji kesukaan modifikasi kue klemben dengan substitusi tepung kelapa - Dini Asropi (Jurnal Kuliner, 2023)
By using an organoleptic test that evaluates surface texture, crumb texture, aroma, and taste of klemben cake with coconut flour as a substitute, this study wants to determine whether the general public will accept it. Observations using organoleptic tests with four levels, namely very like, like, dislike, and dislike is the approach used in this study to collect data. Using a quantitative descriptive approach, the data is evaluated. Research findings regarding people's preferences for klemben cakes in terms of surface texture are included in the "quite similar" category, the crumb texture aspect is in the very like category, the aroma aspect is in the very like category, and the taste aspect is in the very like category, the color aspect is in very like category. Popular approval of coconut flour-based klemben cakes, which meet the standards for dry cakes and can be classified as "reasonably similar", and the public can accept modifications according to the klemben cake.